Radiative gravitational collapse to spherical, toroidal and higher genus black holes - Mena, Filipe C. (2017)
We derive the matching conditions between FLRW and generalised Vaidya spacetimes with spherical, planar or hyperbolic symmetry, across timelike hypersurfaces. We then construct new models of gravitational collapse of FLRW spacetimes with a negative cosmological constant having electromagnetic radiation in the exterior. The final state of the collapse are asymptotically AdS black holes with spherical, toroidal or higher genus topologies. We analyse the collapse dynamics including trapped surface formation, for various examples